Analýza programované buněčné smrti průtokovou cytometrií - Balvan, Jan; Raudenská, Martina; Masařík, Michal; Kizek, René (Journal of Metallomics and Nanotechnologies, 2014)
Programmed cell death (PCD) is a crucial process required for the normal development and physiology of metazoans. The three major mechanisms that induce PCD are called type I (apoptosis), type II (autophagic cell death), and type III (necrotic cell death). Dysfunctional PCD leads to diseases such as cancer and neurodegeneration. Although apoptosis is the most common form of PCD, recent studies have provided evidence that there are other forms of cell death. The high majority of classical apoptotic hallmarks can be rapidly examined by flow cytometry. Cytometry thus became a technology of choice in diverse studies of cellular demise. A large variety of cytometric methods designed to identify apoptotic cells and probe mechanisms associated with this mode of cell demise have been developed during the past two decades.
Keywords: nekróza; Cell Survival; Apoptosis; inhibitory kaspas; viabilita buněk; Annexin A5; Propidium; propidium; průtoková cytometrie; Necrosis; Caspase Inhibitors; apoptóza; Flow Cytometry; annexin A5